Translation readability of the verb phrase with modality in the TikTok privacy policy - Fatikha, Zahwa; Sukaesih, Ina; Indrayani, Septina (Lembaga Penelitian, Penerbitan, Pengabdian dan Pengembangan Masyarakat (LP4M) Unmuha, 2023)
This qualitative descriptive research aims to discuss the types of verb phrases with modality based on Palmer (1990) and Alwi (1992) theory, translation techniques based on theory introduced by Molina and Albir (2002), and translation readability based on theory developed by Nababan (2012) in the TikTok Privacy Policy. The source of data in this study is verb phrases with modality obtained from the webpage on the TikTok website containing the Privacy Policy of the TikTok platform in English and Indonesian versions. The translation readability was discussed through the Focus Group Discussion (FGD). The data were analyzed using the data analysis method by Spradley, consisting of domain, taxonomic, componential, and cultural theme analysis. The linguistic data is the verb phrase with epistemic, dynamic, and deontic modality in the Privacy Policy on the TikTok website. In this research, 100 data of verb phrases with modality were obtained and categorized into three types of modalities; 50 data belong to the deontic modality, 24 data to the dynamic modality, and 18 data to the epistemic modality. Verb phrases with two modalities are also found; 6 data belong to the epistemic and deontic modalities, and 2 data belong to the epistemic and dynamic modalities. Eight translation techniques are adopted, including established equivalent, literal translation, linguistic amplification, transposition, the combination of established equivalent and transposition, the combination of literal translation and transposition, the combination of established equivalent and reduction, and the combination of linguistic amplification and established equivalent. The most used technique is the established equivalent with 62 data or 62% of the total data. The overall readability translation score of verb phrases with modality in the privacy policy has quite high readability, with a score of 2.76.